Georgi Dimitrov : A Biographical Sketch / Stella Blagoeva ; Editor, Vessa Zheliazkova ; Penerjemah, Marjorie Pojarlieva - Blagoeva, Stella; Vessa Zheliazkova; Marjorie Pojarlieva (Foreign Languages Press, 1961)
232 hlm. ; 20,5 cm.